Mekanisme Good Corporate Governance Terhadap Nilai Perusahaan Barang Baku Di Indonesia - Putri Puspita Sari; Ririh Dian Pratiwi (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
The goal of this study is to prove the influence of good corporate governance (GCG) mechanism has on the value of basicmaterial companies listed on Indonesia Stock Exchange (IDX) in 2020-2021. The five independent variables used in this study are independent commissioners, institutional ownership, management ownership, board of directors, and audit committee. Selected through purposive sampling, there were total of 60 samples studied using multiple linear regression analysis as an analytical technique & SPSS 25 as the research tool. The findings from this study reveal that simultaneously the GCG mechanism influences firm value. Partially, managerial and institutional ownership also independent commissioners are three of the five GCG mechanisms that impact company value. Meanwhile the other two; audit committees and boards of directors, have no impact on firm value.